EMPLOYEE ENGAGEMENT DALAM PERSPEKTIF MANAJEMEN MODERN: STUDI KUALITATIF KONSEPTUAL PADA KABUPATEN BOJONEGORO - M Ridlwan Hambali; Lina Amiliya Amiliya; Ahmad Shofiyuddin; Ifa Khoiria Ningrum (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2026)
This study aims to analyze the concept of employee engagement from the perspective of modern management and its relevance to the dynamics of the working environment in Bojonegoro. The research adopts a qualitative conceptual approach through a literature review of relevant scholarly sources published within the last ten years. The findings indicate that employee engagement represents a multidimensional attachment encompassing emotional, cognitive, and behavioral involvement in work, which is influenced by leadership, fairness, role clarity, and supportive work environments. In the context of Bojonegoro, employee engagement plays a crucial role in addressing social changes and increasing demands for professional performance. The implications of this study emphasize the importance of implementing humanistic, adaptive, and contextual human resource management approaches to foster sustainable work engagement. The novelty of this research lies in its conceptual analysis of employee engagement that focuses on theoretical strengthening rather than empirical measurement, while contextualizing the concept within local work dynamics, offering a distinct perspective compared to previous studies that predominantly emphasize quantitative and institution-based analyses.